Culture and Ethnicity: what is the question? - Wepa, Dianne (Cultural safety in Aotearoa New Zealand, 2015)
In this second edition of Cultural Safety in Aotearoa New Zealand, editor Dianne Wepa presents a range of theoretical and practice-based perspectives adopted by experienced educators who are active in cultural safety education. Dianne Wepa, Hawkes Bay District Health Board, NZ.
Keywords: bicultural; ethnic identity; ethnicity

Introduction: Situating mixed race in New Zealand and the world - Webber, Melinda (Mana Tangatarua: mixed heritages, ethnic identity and biculturalism in Aotearoa/New Zealand, 2018)
"This volume explores mixed race/mixed ethnic identities in Aotearoa/New Zealand. Mixed race and mixed ethnic identity are growing in popularity as research topics around the world. This edited collection looks at mixed race and mixed ethnic identity in New Zealand: a unique context, as multiple ethnic identities have been officially recognised for more than 20 years. The book draws upon research across a range of disciplines, exploring historical and contemporary ways in which official and social understandings of mixed race and ethnicity have changed. It focuses on the interactions between race, ethnicity, national identity, indigeneity and culture, especially in terms of visibility and self-defined identity in the New Zealand context. Mana Tangatarua situates New Zealand in the existing international scholarship, positioning experiences from New Zealand within theoretical understandings of mixedness. The chapters develop wider theories of mixed race and mixed ethnic identity, at macro and micro levels, looking at the interconnections between the two. The volume as a whole reveals the diverse ways in which mixed race is experienced and understood, providing a key contribution to the theory and development of mixed race globally."--Provided by publisher.
Keywords: bicultural; ethnic identity; ethnicity; europeans; rangahau o te noho-ā-iwi; social conditions; te ao hurihuri; tikanga | indigenous law; tāngata whenua

Chapter Five – Māori Representation and Participation in National and Local Government Politics - Sullivan, Ann (Indigenous politics: institutions, representation, mobilisation, 2015)
Keywords: ethnic identity; ethnicity; government; government relations; iwi taketake; māori electorates; māori seats; tiriti o waitangi/treaty of waitangi; treaty obligations

Mana Maori motuhake Maori concepts and practices of sovereignty - Mutu, Margaret (Routledge handbook of critical indigenous studies, 2021)
Keywords: colonisation; ethnicity; he whakaputanga; mana motuhake; rangatiratanga

Maori identities; fixed, forced, and fluid - McIntosh, Tracey (New Zealand identities: departures and destinations, 2005)
Social scientists attached to the Centre for Applied Cross Cultural Research at Victoria University of Wellington examine issues of New Zealand identity.
Keywords: ethnic identity; ethnicity; identity